PENGARUH METODE LATIHAN FARTLEK TERHADAP PENINGKATAN DAYA TAHAN AEROBIC PESERTA EKTRAKURIKULER FUTSAL PUTRA - Rusdian Pratama; Mimi Haetami; Muhammad Fachrurrozi Bafadal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrakThe problem in this study is the ability of aerobic endurance for futsal players at SMA Muhammadiyah 1 Pontianak, who take part in futsal extracurriculars are still categorized as lacking and the Fartlek method has not been implemented. The purpose of this study was to find the effect of the Fartlek method on aerobic endurance ability. The population in this study were students who took extracurricular activities at SMA Muhammadiyah 1 Pontianak, amounting to 24 people. Sampling in this study using saturated sampling technique, namely the technique of determining the sample if all the population is used as a sample. The form of research used in this study is a Pre Experimental Design with a One-Group Pretest-Posttest Design model, namely a research design that is given a pretest before being given treatment, so that the results of the treatment can be known more accurately. Based on the calculated chi square for pretest = 10,806 and posttest = 8.834, it is smaller than the chi square table (11,070), then the distribution of statistical data for the 24 athletes can be declared normal, F count is smaller than F table 1.179 <2.01 for F table 0 0.05, it can be concluded that the variance of the data to be analyzed is homogeneous. The calculation of the T test obtained the value of t count = 8,306 > t table = 1,714. The percentage increase in aerobic endurance using the fartlek method is 6.75%. Thus, the conclusion of this study is that increasing aerobic endurance by using the fartlek method has been shown to have an effect on increasing the aerobic endurance of students who take part in futsal extracurricular at SMA Muhammadiyah 1 Pontianak.Keywords: Fartlek, endurance